The effect of steel fiber as addition reinforcement in reinforced concrete beam - Nur Izzati Binti Mahmud (School of Environmental Engineering, University Malaysia Perlis, 2014)
Steel fiber reinforced concrete has been increasingly used in structural applications during the last four decades. It is generally accepted that addition of steel fibers significantly increases tensile toughness and ductility, also slightly enhances the flexural strength. Effects of steel fibers as addition reinforcement in reinforced concrete (RC) beams are the main objectives of this study.